2007
DOI: 10.1002/jbm.a.31789
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of metal ion‐induced DNA damage, apoptosis, and necrosis in human (Jurkat) T‐cells demonstrates Ni2+ and V3+ are more toxic than other metals: Al3+, Be2+, Co2+, Cr3+, Cu2+, Fe3+, Mo5+, Nb5+, Zr2+

Abstract: It remains unclear how metal released from implants affects cells of the immune system and, in particular, cells of the adaptive immune system, that is, T-helper lymphocytes. In this study, we investigated the effects of aluminum, chromium, cobalt, copper, iron, molybdenum, nickel, niobium, vanadium, and zirconium ions at concentrations from 0.05 to 5.0 mM on human CD4+ T lymphocytes. The DNA damage, apoptosis, necrosis, and proliferation responses of a human T-helper lymphocyte (Jurkat) cell line were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 38 publications
6
58
1
1
Order By: Relevance
“…Nonetheless, in 72 h, the early apoptotic rate and Caspase mRNA level of the Pdbased group were both higher than those of the negative groups (p<0.05). This is probably a consequence of copper in Pd-based alloy, which has been reported to be the cause of cell apoptosis 19) . Regarding the CP-Ti alloy, the early apoptotic rate was significantly higher than that of the negative group and so as the activation of Caspase 9 and Caspase 3 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in 72 h, the early apoptotic rate and Caspase mRNA level of the Pdbased group were both higher than those of the negative groups (p<0.05). This is probably a consequence of copper in Pd-based alloy, which has been reported to be the cause of cell apoptosis 19) . Regarding the CP-Ti alloy, the early apoptotic rate was significantly higher than that of the negative group and so as the activation of Caspase 9 and Caspase 3 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, increase in sub-G1 fractions at 150 and 300 M Ni 2ϩ could be indicative of apoptotic cell death, an event also associated to blastocyst development and LIF withdrawal-induced mouse ES cell differentiation (10,15,33,39). Alternatively, apoptosis could be caused by toxicity induced by Ni 2ϩ exposure (6). It is important to note that the differentiation effect induced by Ni 2ϩ was only clearly observed at concentrations an order of magnitude higher than those required to selectively block recombinant Ca v 3.2 channels (IC 50 ϳ5-10 M) (21).…”
Section: Discussionmentioning
confidence: 99%
“…Caicedo et al (2008), De Boeck et al (1998), Hartwig et al (1990Hartwig et al ( , 1991 and Ponti et al (2009) all reported induction of DNA damage by cobalt chloride in human Jurkat cells by the neutral comet assay, in isolated human lymphocytes using the alkaline comet assay, in HeLa cells by nucleoid sedimentation in sucrose density gradients, and in Balb/3T3 cells by the comet assay, respectively. De Boeck et al (1998) and Van Goethem et al (1997) also reported induction of direct DNA damage with low concentrations of ultrafine cobalt metal in human leukocytes and blood lymphocytes from three different donors using the alkaline version of the comet assay, although in a later paper, De Boeck et al (2003a) were unable to reproduce the DNA damage responses.…”
Section: Studies In Mammalian Cells In Vitromentioning
confidence: 95%